DAMPAK KEBERADAAN PASAR MODREN TERHADAP KINERJA EKONOMI REGIONAL - Rasidin Karo-Karo Sitepu (Universitas Negeri Medan, 2012)
The objective of study is to analyze the impact of modern market presence to performance of regional economic. Specification model using simultaneous equations and is suspected by the method of two stages least Squares. Using secondary data for series from 1980 to 2010. The results showed that the presence of a modern market significantly negative effect on the turnover of MSMEs trade sector. Conversely a positive impact on MSME sector of agriculture and manufacture. Scenario modern market presence is significantly negative effect on traditional markets. Number of traditional markets and local government original receipt (PAD) will be decrease. However, overall gross regional domestic product (PDRB) and purchasing power parity are increased, while the number of unemployed decreased. To reduce the negative impact of modern market presence can be done by restricted the license of modern markets, increased access to capital, increased market access by doing a partnership with a modern market.